The Phenomena of Money Politics and Identity Politics Ahead of the 2024 Elections - Andre Agasi; Robert Sibarani; Erond Litno Damanik (Universitas of Muhammadiyah Makassar, 2023)
General elections should be a forum for the aspirations of the people, but in practice General elections are used as a place to compete for seats in government. In the previous elections, money politics and identity politics continued to occur, so it is feared that the 2024 elections will be tarnished by the rampant money politics and identity politics. This paper tries to discuss money politics during the quiet period and identity politics as a challenge to Indonesian democracy. This research uses a literature study. This research uses a qualitative approach and the research source uses secondary data. This paper focuses on the practice of money politics during the quiet period played by political elites. In addition, identity politics is also feared to be a challenge for the 2024 elections. Actions in politics create issues of ethnicity, religion, and race as a form of political identity to gain support from the people.